Young people’s identity & Facebook behaviour: The role of gender and ethnicity - Rambaree, Komalsingh (Cogent social sciences, 2017)
The aim was to investigate the effects of gender and ethnicity on Facebook visit and identity among young people (14-25 years old) living in Mauritius. According to the results obtained, males were shown to visit more Facebook and had a stronger Facebook identity than did females. However, females compared to males considered themselves to be persons that are more similar online as offline, and their Facebook activity represented more who they were than it did for males. Hindu participants were shown to most infrequently visit Facebook. They were also the group with the weakest Facebook identity. Creole and Muslim groups were reported to have the strongest Facebook identity followed by the Mixed participants. This study concludes that both gender and ethnicity might have a significant impact on Facebook activity and identification among young people.